1996
DOI: 10.1042/bj3140215
|View full text |Cite
|
Sign up to set email alerts
|

Inositol phosphates in the duckweed Spirodela polyrhiza L

Abstract: We have undertaken an analysis of the inositol phosphates of Spirodela polyrhiza at a developmental stage when massive accumulation of InsP6 indicates that a large net synthesis is occurring. We have identified Ins3P, Ins(1,4)P2, Ins(3,4)P2 and possibly Ins(4,6)P2, Ins(3,4,6)P3, Ins(3,4,5,6)P4, Ins (1,3,4,5,6)P5, D- and/or L-Ins(1,2,4,5,6)P5 and InsP6 and revealed the likely presence of a second InsP3 with chromatographic properties similar to Ins(1,4,5)P3. The higher inositol phosphates identified show no obv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
87
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 37 publications
7
87
0
Order By: Relevance
“…9) (8). One is an inositol lipid-independent pathway that occurs through sequential phosphorylation of inositol 3-phosphate, or possibly inositol itself, through a series of proposed intermediates based on studies in duckweed and slime mold (13,14). A second is through a phospholipase Cmediated or lipid-dependent pathway that converts PIP 2 to IP 3 and then phytate through multiple routes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9) (8). One is an inositol lipid-independent pathway that occurs through sequential phosphorylation of inositol 3-phosphate, or possibly inositol itself, through a series of proposed intermediates based on studies in duckweed and slime mold (13,14). A second is through a phospholipase Cmediated or lipid-dependent pathway that converts PIP 2 to IP 3 and then phytate through multiple routes.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemically, I(1,4,5)P 3 , I(1,3,4,5)P 4 , and I(1,3,4,5,6)P 5 kinase activities have been described in pea roots and immature soybean seeds, respectively, (10 -12), but none of the corresponding genes have been identified. Several studies have indicated that IP 6 may also be synthesized in lipid-independent pathways directly from inositol and/or inosi-tol 3-phosphate (13,14). Despite this, only one IP kinase from any plant species has been cloned and this Arabidopsis gene product has I(1,3,4)P 3 5/6-kinase activity (15).…”
mentioning
confidence: 99%
“…Several species of floating macrophytes including Spirodela sp. [82] and Azolla sp. [83] have been found to contain either inositol phosphates, enzymes necessary for the synthesis of IHPs, or both.…”
Section: Quantificationmentioning
confidence: 99%
“…Pathways I and II originate from the hydrolysis of PI(4,5)P 2 by phospholipase C and are therefore lipid-dependent. Pathway III is a lipid-independent pathway that involves the sequential phosphorylation of I(3)P or inositol (21,38). The majority of the participating kinases in this pathway are unknown at the molecular level.…”
Section: Atipk1mentioning
confidence: 99%
“…However, the failure to identify a I(1,4,5)P 3 3-kinase activity or gene ortholog in plants has challenged the existence of pathway (II). Pathway (III) has been proposed in Dictyostelium discoideum and Duckweed (21,22), is lipid͞lipase-independent, and occurs through the sequential phosphorylation of I(3)P or free myo-inositol. Recent work has identified a kinase activity with possible relevance to Pathway (III) (23).…”
mentioning
confidence: 99%